Paleozoic to present-day kinematic evolution of the frontal part of the Andes between parallels 23º and 24º S (Jujuy province, Argentina) - Seggiaro, R. E.; Bulnes, M.; Poblet, J.; Aguilera, N. G.; Rodríguez-Fernández, L. R.; Heredia, N.; Alonso, J. L. (TRABAJOS DE GEOLOGÍA, 2010)
A geological map and a transect across the thick-skinned Eastern Cordillera and the transitionbetween the thin-skinned Subandean Ranges and the thick-skinned Santa Barbara System (all ofthem NNE-SSW striking) interfered by the NE-SW trending rift called Lomas the Olmedo Trough,at a latitude comprised between 23º S and 24° S, were constructed. The available data allowed us toillustrate the geometry and the kinematic evolution of the structures formed during three main tectonicevents recorded in this region: a Cenozoic contractional event (Andean orogeny), an extensionalCretaceous event and a Paleozoic event (?).